Development and characterization of two human triple‐negative breast cancer cell lines with highly tumorigenic and metastatic capabilities. (18th January 2016) - Su, Yanrong; Pogash, Thomas J.; Nguyen, Theresa D.; Russo, Jose
Abstract: Triple‐negative breast cancer (TNBC) is a group of cancer with high diversity, limited therapies, and poor prognosis. TNBC cell lines and animal models provide effective tools for studies and drug discovery. Here, we report the development of two TNBC cell lines (XtMCF and LmMCF) based on our existing cell model that consists of normal breast epithelial cell line MCF10F, estradiol‐transformed cells trMCF, and Boyden chamber‐selected tumorigenic cells bsMCF. The XtMCF and LmMCF cell line were derived from xenograft and lung metastasis of bsMCF cells, respectively. The bsMCF, XtMCF, and LmMCF cells have undergone epithelial–mesenchymal transition (EMT), exhibiting a mesenchymal‐like feature. In vivo studies showed XtMCF and LmMCF cells were highly tumorigenic and metastatic. The injection of 5 × 10 4 cells to CB17/SCID mice mammary fat pad produced xenografts in 9/9 mice and tumors reached 10 millimeters in diameter in 5 weeks. The injection of 1 × 10 6 XtMCF or 8 × 10 4 LmMCF cells into the mice tail vein was sufficient to form extensive lung metastases in 4 weeks. The two new cell lines exhibited CD44 + /CD49f + and CD44 + /EpCAM + cancer stem cell (CSC) characteristics, and the EGF‐like domain of EpCAM was cleaved off. Together with the normal and early transformed counterparts, herein we provide a complete cancer model for the study of initiation, evolution, and identification of new therapeutics for TNBC. The finding that EGF‐like domain of EpCAM was cleaved off in cells which have undergone EMT suggests this cleavage may be involved in the EMT process and the cancer stem cell properties of these cells. Abstract : The authors developed and characterized two highly tumorigenic and metastatic triple‐negative breast cancer (TNBC) cell lines (XtMCF and LmMCF). The two new cell lines have undergone epithelial–mesenchymal transition (EMT), exhibiting a mesenchymal‐like feature and CD44+/CD49f+ and CD44+/EpCAM+ cancer stem cell characteristics, and the EGF‐like domain of EpCAM is cleaved off.